(3GdcGajIs - (3GdeGdcj GdeUQj GdCSfhj, CHh YeQh, GHf GdMGLH, LeGd GdOjf, YKeGf Hf YeQ Hf CHj HcQ, J(B646(3g`s ((3EHQGgje Hf eUWais)
(3ChdgG (B:s
(3GdcdeI daX hVY deYfi eaQO hgj GSe haYd hMQa dCfgG EeG Cf JOd Ydi eYfi aj faSgG Ch dG GdKGfj GdMQa GdChd EeG Cf jbJQf HCMO GdCRefI GdKdGKI Ch dG, GdKGfj GdGSe hGdChd GdaYds
(3BNQgG (B:s
(3cGdefaU aEf de jcf acGdeJUd hef KeI bjd gd JQjf hJhf hJQjfj hCYRhf (B((3cPG(B) (3hCYRf (B((3cPG(B) (3hGdeNaaI JMPa ddSGcf haj Gdhba ajQO eG MPa hGdeaJhM eG bHdgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 211s
(3eYLe GdeDdajf(B: 2 / 366s
(3cTa GdXfhf(B: 2 / 1370s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs